ANALISIS KINERJA STRUKTUR GEDUNG BERTINGKAT AKIBAT BEBAN GEMPA DENGAN METODE RESPONS SPEKTRUM DAN TIME HISTORY (Studi kasus : Gedung Infrastruktur BASICS LIPI 3 Bandung) - Taufik Hidayat, - (2022)
Indonesia is a country surrounded by the confluence of three major world plates, namely, the Indo-Australian plate, the Eurasian plate, and the Pacific plate. Geologically, in such an area there will be many geological structures such as fractures and faults. The risk due to the geological structure is that it is prone to earthquakes. Strong earthquakes can cause buildings to collapse and take lives and earthquakes occur suddenly and can not be predicted. Therefore, the building should be built with the concept of an earthquake-resistant building. This study aims to determine the level of performance of the building structure. The spectrum response method and time history are used to analyze the structure of earthquake-resistant structures, and the capacity spectrum method is used to evaluate the structure's performance against the planned earthquake (ATC-40). The case study building is the BASICS LIPI 3 Bandung, which has 6 stories and is located in Bandung. RSAP 2020 was used for structural modeling and analysis. The San Fernando earthquake, the Loma Prieta earthquake, and the Superstition earthquake were all presented as examples of earthquake records. Based on the results of the analysis of the maximum deviation using the response spectrum method, the deviation was 3,98 cm for the X direction and 3,78 cm for the Y direction. Meanwhile, the largest deviation for the time history technique was 2,838 cm in the X direction and 3,91 cm in the Y direction in the San Fernando earthquake. The maximum total deviation is 0,00159 m, and the inelastic deviation is 0,00148 m. So that it shows that the level of performance of the structure of the Cisauk Point Apartment Tower Anami 1 based on ATC-40 is Immediate Occupancy (IO), which means that the structure is in a safe condition and that the overall plan of the building is not damaged and can be used immediately in the event of an earthquake with an earthquake strength. Keyword: High-rise building, structural behavior, spectrum response, time history, ATC-40